CDR3 loop flexibility contributes to the degeneracy of TCR recognition. - Reiser, J; Darnault, C; Grégoire, C; Mosser, T; Mazza, G; Kearney, A; Van Der Merwe, P; Fontecilla-Camps, J; Housset, D; Malissen, B (2003)
T cell receptor (TCR) binding degeneracy lies at the heart of several physiological and pathological phenomena, yet its structural basis is poorly understood. We determined the crystal structure of a complex involving the BM3.3 TCR and an octapeptide (VSV8) bound to the H-2K(b) major histocompatibility complex molecule at a 2.7 A resolution, and compared it with the BM3.3 TCR bound to the H-2K(b) molecule loaded with a peptide that has no primary sequence identity with VSV8. Comparison of these structures showed that the BM3.3 TCR complementarity-determining region (CDR) 3alpha could undergo rearrangements to adapt to structurally different peptide residues. Therefore, CDR3 loop flexibility helps explain TCR binding cross-reactivity.